The Influence of Intellectual Capital and Investment Decisions on Company Value in Telecommunications Sub-Sector Companies Listed on The Indonesian Stock Exchange Period 2018-2023 - Dewi, Wulan Sari; Kusumawardhani, Aninditha Putri; Musadat, Irfan Achmad (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
This study aims to find out the picture and influence of Intellectual Capital and Investment Decisions on Company Value. The object of this research is telecommunications subsector companies listed on the IDX (Indonesia Stock Exchange) for the 2018-2023 period. The method used is a quantitative method with a descriptive and verifiable approach. The population in this study is 132 financial statements and annual reports from 22 telecommunications subsector companies listed on the IDX (Indonesia Stock Exchange) for the 2018-2023 period, with a purposive sampling technique, so that the sample in this study totals 18 financial statements from 3 companies during the 2018-2023 period. The results of this study show that the value of Intellectual Capital and Investment Decisions on Company Value fluctuates. Based on the results of the hypothesis test, it was found that the results of the t-test partially the Intellectual Capital variable influenced the Company's Value with an influence of 29.6%. Meanwhile, the Investment Decision variable had no effect on the Company's Value with an influence of 0.7%, and simultaneously the result was obtained that Intellectual Capital and the Investment Decision has no effect on the Company's Value in Telecommunications Subsector Companies Listed on the IDX (Indonesia Stock Exchange) for the 2018-2023 Period with an influence of 23.5%.